Improving the precise motor skills of aircraft control hands - Meshcheryakov A.V. ,; Salimzyanov R.R. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the optimal way to hold the drone controller sticks and develop a set of exercises to improve piloting skills. Methods and structure of the study. The drone operators showed well-developed small muscles of the forearms and hands involved in controlling the drone. The dominant and most effective ways of holding the controller and manipulating the joysticks while piloting the drone were identified. Exercises aimed at improving fine motor skills were selected. The experiment involved students of the first and second years of study at the Ulyanovsk Institute of Civil Aviation. Sociological tools (interviews, questionnaire filling), analytical and synthetic approaches, as well as the competitive method were used. Results and conclusions. When analyzing the control of the UAV using the control panel, it was found that the main load is carried by the following muscle groups of the hands: the muscles of the middle part of the hand, the muscles of the posterior surface of the forearm (both superficial and deep), the deep muscles of the anterior surface of the forearm, as well as the muscles controlling the movements of the thumb. It has been experimentally confirmed that using the pinch grip of the sticks provides increased control accuracy, while controlling the sticks with only the thumbs allows for a higher reaction speed. The majority of students (70%) prefer the pinch control method. The introduction of specialized physical exercise complexes into the educational process enabled the team of cadets from the experimental group to demonstrate high results in UAV piloting competitions.